Estimation of N-acetyltransferase 2 haplotypes - Hermann M. Bolt; Doris Dannappel; Meinolf Blaszkewicz; Mirabutaleb Samimi; Klaus Golka; Silvia Selinski (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
N-Acetyltransferase 2 (NAT2) genotyping may result in a considerable percentage in several ambiguous allele combinations. PHASE 2.1 is a statistical program which is designed to estimate the probability of different allele combinations. We have investigated haplotypes of 2088 subjects genotyped for NAT2 according to standard PCR/RFLP methods. In 856 out of 2088 cases the genotype was clearly defined by PCR/RFLP only. In many of the remaining cases the program clearly defined the most probable allele combination: In the case of *5A/*6C, *5B/*6A the probability for *5B/*6A is 99% whereas the alternative allele combination *5A/*6C can be neglected. Other combinations cannot be allocated with a comparable high probability. For example the allele combination *5A/*5C, *5B/*5D provides for *5A/*5C a probability of 69% whereas the estimation for *5B/*5D allele is only 31%. In the two most often observed constellations in our data [(*12A/*5B, *12C/*5C); (*12A/*6A, *12B/*6B, *4/*6C)] the probability of allele combination was ascertained as follows: *12A/*5B, 98%; *12C/*5C, 1.4% and *12A/*6A, 82%; *4/*6C, 17%; *12B/*6B, 0%. The estimation of the NAT2 haplotype is important because the assignment of the NAT2 alleles *12A, *12B or *13 as a rapid or slow genotype has been discussed controversially. Otherwise the classification of alleles in subjects which are not showing a clearly allocation can result in a rapid or slow acetylation state. This assignment has an important role in survey of bladder cancer cases in the scope of occupational exposure with aromatic amines.
Keywords: 519; PHASE 2.1; NAT2 genotyping; single nucleotide polymorphism